(untitled) (Physical Education, Health and Social Sciences, 2025)
Around the world, malaria is a major health worry in many developing countries such as Pakistan. The purpose of this study design was to find the percentage of cases of malaria among people living in District Hyderabad, Sindh, Pakistan. During the period from 1 January to 30 June, 2024, a descriptive study was carried out. We gathered the data from the District Health Office of the District. The statistical work in this paper was done using MS Excel 2016. In all, 93029 people with suspected malaria were registered. Approximately 56.74% of all positives in these totals were males and 43.25% were females. Of the total positive cases (92.55%), Plasmodium vivax was identified, with Plasmodium falciparum accounting for (6.9%) of the remaining cases. According to age groups, 59.41 percent of cases were reported in people 15 years or older. More than a quarter of the cases were reported in May which was the highest and just a tenth in February which had the lowest number. Overall, the data showed that men were more likely to be infected, with the most cases seen in people ages 15 and older. In District Hyderabad, P. vivax is the main species.